Черное белое: роман / Н. В. Андреева - Андреева Наталья Вячеславовна (АСТ, 2007)
Экземпляры: АБ (20110920) / Инвентарный номер: 39949zzzzz / Цена: 120.00 / Сис.шифр: 84(2) / Авт.знак: А 65 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)